The DUF1669 domain of FAM83 family proteins anchor casein kinase 1 isoforms - Fulcher, Luke J; Bozatzi, Polyxeni; Tachie-Menson, Theresa; Wu, Kevin Z L; Cummins, Timothy D; Bufton, Joshua C; Pinkas, Daniel M; Dunbar, Karen; Shrestha, Sabin; Wood, Nicola T; Weidlich, Simone; Macartney, Thomas J; et al. (Science signaling, 2018)
Members of the casein kinase 1 (CK1) family of serine-threonine protein kinases are implicated in the regulation of many cellular processes, including the cell cycle, circadian rhythms, and Wnt and Hedgehog signaling. Because these kinases exhibit constitutive activity in biochemical assays, it is likely that their activity in cells is controlled by subcellular localization, interactions with inhibitory proteins, targeted degradation, or combinations of these mechanisms. We identified members of the FAM83 family of proteins as partners of CK1 in cells. All eight members of the FAM83 family (FAM83A to FAM83H) interacted with the α and α-like isoforms of CK1; FAM83A, FAM83B, FAM83E, and FAM83H also interacted with the δ and ε isoforms of CK1. We detected no interaction between any FAM83 member and the related CK1γ1, CK1γ2, and CK1γ3 isoforms. Each FAM83 protein exhibited a distinct pattern of subcellular distribution and colocalized with the CK1 isoform(s) to which it bound. The interaction of FAM83 proteins with CK1 isoforms was mediated by the conserved domain of unknown function 1669 (DUF1669) that characterizes the FAM83 family. Mutations in FAM83 proteins that prevented them from binding to CK1 interfered with the proper subcellular localization and cellular functions of both the FAM83 proteins and their CK1 binding partners. On the basis of its function, we propose that DUF1669 be renamed the polypeptide anchor of CK1 domain.